Brexit, COVID-19 and climate change: mapping the impact of the 'triple challenge' on health and well-being in wales. Issue 2 (4th March 2023) - Green, Liz; Ashton, Kathryn; Azam, Sumina; Clemens, Timo; Bellis, Mark
ABSTRACT: Brexit, COVID-19 and climate change pose challenges of national and global importance. They continue to have impacts across the economy, society, health, and the environment, all of which are determinants of health and well-being. Between 2018 and 2021, Public Health Wales undertook three Health Impact Assessments (HIA) in relation to the impact of the challenges in Wales. Based on these, work has been carried out to map the synergies across the 'Triple Challenge'. This paper highlights the commonalities in the impact of the three challenges for Wales, discusses the process carried out, learns from it and proposes actions that can be taken to mitigate harm. Results indicate the three components of the Triple Challenge must not be viewed as separate silos as they have cumulative multi-faceted impacts. This affects some population groups more negatively than others and present a 'Triple Challenge' to nation states in the UK and Europe. A HIA approach can enable a range of stakeholders to critically view similar challenges not just as single issues but as a holistic whole to mobilise action.